2017
DOI: 10.4103/ijdr.ijdr_534_16
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor: Role in human cancer

Abstract: Cells are constantly exposed to various external stimuli which regulate the growth and survival of the cells. The signal transduction from the external environment to the interior of the cell is carried out by cell surface or transmembrane receptors. Epidermal growth factor receptor (EGFR) is a type I receptor tyrosine kinase and along with its ligands, EGFR is involved in the regulation of multiple cellular pathways. EGFR and its signaling pathway have been studied extensively for the biological and pathophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…EGFR was the first member of the ErbB family to be discovered, and it plays a significant role in many cellular processes essential for survival and cell growth. EGFR is also known to be involved in the pathogenesis and progression of different types of cancers [ 105 ] and in promoting immune escape through different mechanisms, such as the upregulation of PD-L1, the downregulation of tumor antigen presentation, and the induction of secretion of metabolites and molecules with immunosuppressive properties in the TME [ 106 ]. Therefore, mutations in this receptor may be associated with nonresponse to ICI therapy [ 107 , 108 ], but the possible link between EGFR and HPD remains unknown.…”
Section: Possible Tumor-related Mechanisms Of Hpdmentioning
confidence: 99%
“…EGFR was the first member of the ErbB family to be discovered, and it plays a significant role in many cellular processes essential for survival and cell growth. EGFR is also known to be involved in the pathogenesis and progression of different types of cancers [ 105 ] and in promoting immune escape through different mechanisms, such as the upregulation of PD-L1, the downregulation of tumor antigen presentation, and the induction of secretion of metabolites and molecules with immunosuppressive properties in the TME [ 106 ]. Therefore, mutations in this receptor may be associated with nonresponse to ICI therapy [ 107 , 108 ], but the possible link between EGFR and HPD remains unknown.…”
Section: Possible Tumor-related Mechanisms Of Hpdmentioning
confidence: 99%
“…The role of EGFR signaling in various kinds of malignant tumors has been well elucidated, and Ras/Raf/MEK/ERK is one of the classic downstream pathways of EGFR signaling. 32 34 Our results showed that p-MEK could also be upregulated by ZNF259. Thus, ZNF259 may participate in the upstream regulation of Ras/Raf/MEK/ERK pathway.…”
Section: Discussionmentioning
confidence: 61%
“…40 Head and neck cancers including oral cancer exhibit an increased EGFR expression. [18][19][20][21] Specific binding of gold nanorods to oral cancer cells is achieved by conjugating with Cetuximab, a chimeric monoclonal mouse-human immunoglobulin G1 (IgG1) antibody. Cetuximab binds specifically to the extracellular ligand-binding domain of EGFR with a binding affinity that is two log units greater than that of EGF or TGF-α.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 GNRs bio-conjugated to anti-epidermal growth factor receptor (C-GNR) monoclonal antibodies are supposed to attach exclusively to OSCC cells expressing high concentration of EGFR, making them an ideal target for C-GNRs. [18][19][20][21] We have recently described on paraffinembedded tissue sections of OSCC incubated with C-GNRs, a significant increase in light absorption using diffusion reflection (DR) measurements following illumination with a red color laser beam. 16,17 In vivo studies are needed to investigate the accuracy and applicability of these nanomedical methods in clinical use.…”
Section: Introductionmentioning
confidence: 99%